Конина у системі харчових заборон українців - Артюх Л. (Народна творчість та етнографія, 2005)
Ritual prohibitions are depicted as essential elements in the system of folk eating habits. The classification of the prohibitions is stated: the division into prohibitions on the subject and the object of the action, time bans. The author makes conclusions as for the different character of the eating of horse meat before and after the Baptizm of Rus on the materials of archaeological and written data. Another eating ban (to eat animal blood) is depicted for comparing. The conclusions about the different ways of the development of the prohibitions is made.